Penerapan Building Information Modeling (BIM) sebagai Sistem Informasi dalam Peningkatan Kinerja Pemeliharaan Bendungan - Saleh, Toha; Latief, Yusuf; Sutjiningsih M, Dwita; Rohmatul F, Diana (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Dams are critical infrastructure that faces maintenance challenges due to resource limitations, fragmented data, and inefficiencies in workflow management. Building Information Modeling (BIM), by integrating multidimensional data, offers a promising solution to address these challenges by improving maintenance operations through better data visualization, coordination, and decision-making. The purpose of this study is to investigate how BIM can improve the efficiency and performance of dam maintenance operations in Indonesia. This study uses a mixed method approach, which combines qualitative and quantitative methods. Data was collected through semi-structured interviews with dam maintenance experts and engineers, as well as field observations of projects that implemented BIM. The analysis also involves a review of relevant literature on global BIM applications. Quantitative data is analyzed using statistical tools, while qualitative data is coded to identify key insights and themes. The results show that BIM significantly improves dam maintenance efficiency by optimizing maintenance scheduling, resource allocation, and structural monitoring. BIM's 3-Dimensional (3D) modeling capabilities enable early detection of structural problems, improve safety, and reliability. In addition, the study identifies scalability challenges for small-scale projects and recommends tailored solutions to ensure wider deployment. This research contributes to the development of sustainable maintenance strategies for critical infrastructure, especially in developing countries such as Indonesia.